STRATEGIES FOR INCREASING PARTICIPATION IN THE IMPLEMENTATION OF THE AUTP PROGRAM IN KUDUS REGENCY - Wiludjeng Roessali; Arin Nikmah; Agus Setiadi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
One of the goals of national development is the achievement of national food security. The AUTP program is expected to be able to help rice farmers by making farmers independent, not only dependent on assistance programs so that the AUTP program is also able to achieve farmer independence. There are still many obstacles and problems in implementing AUTP, such as farmers who do not fully understand the benefits of the insurance program, limited human resources so that the possibility of socialization to farmers is not optimal. The purpose of this researcher is to formulate a strategy for developing the AUTP program in Kudus Regency. To formulate priority strategies in increasing the participation of the AUTP program in Kudus Regency. The analysis used includes SWOT and AHP by determining the respondents purposively. The results of the SWOT analysis research show that the SO strategy is to support aggressive and alternative growth, the priority strategy that must be implemented is cheap farmer premium facilities, so that it is not burdensome in terms of financial.